Чингис хааны Дундад Ази руу хийсэн аян дайнд Елюй Чуцай оролцсон нь (1219-1227) (Journal of International Studies, 2003)
English title: Yeh-lu Chu‘tsai in the mission of Chingis khaan to the Middle Asia